2006
DOI: 10.1111/j.1744-7402.2006.02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Delamination Progression in Thermal Barrier Coatings by Mid‐Infrared Reflectance Imaging

Abstract: Mid‐infrared (MIR) reflectance imaging is shown to be a reliable diagnostic tool for monitoring delamination progression in thermal barrier coatings (TBCs). MIR reflectance imaging utilizes the maximum transparency of TBCs in the 3–6 μm wavelength region to probe below‐surface delamination crack propagation that is typically hidden from visible wavelength inspection. The image contrast that identifies delamination progression arises from the increased reflectance produced by a large component of total internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…In the case of the YSZ films a transmittance maximum is found around 4-6 m for both PS [11,26] and EB-PVD [3] coatings.…”
Section: Semi-transparent Spectral Region ( < 9 M)mentioning
confidence: 90%
“…In the case of the YSZ films a transmittance maximum is found around 4-6 m for both PS [11,26] and EB-PVD [3] coatings.…”
Section: Semi-transparent Spectral Region ( < 9 M)mentioning
confidence: 90%
“…The reflectivity at the TBC/air gap interface at the back of a delaminated (unbacked) TBC is very high because a large fraction of the incident light has an angle of incidence above the critical angle for total internal reflection due to the large difference in index of refraction, n, between the TBC (n = 2.2 at 500 nm wavelength for 8YSZ) and air (n = 1.0). This difference in index of refraction can be used to predict [7] the diffuse reflectivity at the back side of the respectively. This shows that just a few backside reflections, caused by TBC internal scattering, will greatly accentuate the contrast between regions of attached and delaminated TBC.…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods are much more successful for probing through the thickness of electron-beam physical vapor deposited (EB-PVD) TBCs than for probing through the much more highly scattering plasma-sprayed TBCs. [5] While midinfrared (MIR) reflectance [6][7] was shown to detect the increased reflectance at 4 μm wavelength that accompanies subsurface crack propagation in plasma-sprayed TBCs, the relative increase in overall reflectance associated with TBC delamination was modest due to the presence of strong background scattering from the pre-existing porosity and cracks present throughout the TBC. This background volume scattering cannot be distinguished from scattering by subsurface delamination cracks, making delamination monitoring difficult for thicker plasma-sprayed TBCs.…”
Section: Introductionmentioning
confidence: 99%
“…The impurities such as Ti, Cr and Fe elements from Fecralloy substrates mainly exist in the equiaxed and columnar zone in TGO scales [42][43][44][45][46][47]. Quadakkers et al [48] demonstrated that the incorporation of Zr or Y promoted the alumina growth with columnar grains.…”
Section: Microstructure Analysis Of Thermally Grown Oxide (Tgo)mentioning
confidence: 99%